Chronicity and the patient's decision-making work. The case of an advanced cancer patient. Issue 1 (2nd January 2022) - Besle, Sylvain; Sarradon-Eck, Aline
Abstract: This paper focuses on the particular situation of an advanced cancer patient whose condition has taken a chronic turn. We argue that chronicity of this kind sometimes falls at the frontier of Evidence Based Medicine because the uncertainty about the patient's condition can lead physicians to resort to clinical trials or non-licensed drugs to prevent the disease from progressing. This situation leaves plenty of scope for individual adjustments between patients and their doctors. Advanced cancer is regarded here not just as a biological event but as a chronic illness and a 'negotiated reality'. We argue that the chronicity of advanced cancer patients' situation broadens the patients' scope for 'work', and we have called this specific type of patient's work 'decision-making work'. This paper is based on a case study focusing on Patrick, a middle-aged Frenchman with metastatic lung cancer who underwent oncological treatment for seven years and was strongly determined to find new therapeutic options even if this meant having to go abroad. He actively orchestrated his therapeutic itinerary by reorganising his relationships with the medical world and coordinating the physicians' work. His particular social position enabled Patrick to bypass some of the current medical rules and to reorganise the usual pattern of distribution of medical responsibilities. The chronicity of his condition placed him at the very frontier of the health care system.